Creación de una empresa productora y comercializadora de arroz en el cantón Montalvo provincia de Los Ríos. - Estrella Paredes, Gilo Raúl (2019)
The productive activity of the company looked for the acceptance of both local and national public, it will compete in the market with large national brands, through the creation of a new rice brand, made with the highest standards of quality, price, and benefits. Through its production and marketing, this activity has become a business opportunity, due to the fact that rice production currently contributes to the country's agricultural and economic growth. A business plan applied for the realization and later development of the project. The analysis of the economic, political, technological, socioeconomic factors were be carried out, identifying the beneficial results for the project. The consumers’ needs and high demand of the country gives way to the opportunity to enter the market a new brand. The financial analysis was carried out by determining that the project is profitable with a Net Present Value (NPV) of USD 2.113,99 and with an Internal Rate of Return (IRR) of 11,20%, in the same way, the prices were adjusted according to the market with a margin of tolerance of ± 2%, due to the acceptance in the market and the response of consumers to the product, the cost or benefit ratio is 1,20. Investors will get a profit of USD 0,20 cents, for each invested dollar.